Plasma-generated reactive oxygen and nitrogen species can lead to closure, locking and constriction of the Dionaea muscipula Ellis trap - Volkov, Alexander G. (J R Soc Interface, 2019)
Reactive oxygen and nitrogen species (RONS) can influence plant signalling, physiology and development. We have previously observed that an argon plasma jet in atmospheric air can activate plant movements and morphing structures in the Venus flytrap and Mimosa pudica similar to stimulation of their mechanosensors in vivo. In this paper, we found that the Venus flytrap can be activated by plasma jets without direct contact of plasma with the lobe, midrib or cilia. The observed effects are attributed to RONS, which are generated by argon and helium plasma jets in atmospheric air. We also found that application of H(2)O(2) or HNO(3) aqueous solutions to the midrib induces propagation of action potentials and trap closing similar to plasma effects. Control experiments showed that UV light or neutral gas flow did not induce morphing or closing of the trap. The trap closing by plasma is thus likely to be associated with the production of hydrogen peroxide by the cold plasma jet in air. Understanding plasma control of plant morphing could help design adaptive structures and bioinspired intelligent materials.